1941
DOI: 10.1172/jci101209
|View full text |Cite
|
Sign up to set email alerts
|

On the Renal Tubular Excretion of Creatinine in Normal Man1

Abstract: The demonstration that in man the renal excretion of exogenous creatinine 1 takes place in part by an active tubular process depends upon two experimental findings (1). The plasma clearance of creatinine in the normal individual is invariably in excess of the simultaneously determined inulin clearance, which is accepted as a valid measure of glomerular filtration rate (2). Furthermore, raising the plasma creatinine from low to high concentrations depresses its clearance toward that of inulin, which appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1948
1948
1969
1969

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…This conclusion extends the evidence for the tubular excretion of creatinine as advanced by Shannon (21) and Shannon and Ranges (27), and confirms that reviewed elsewhere on the mechanism of excretion of inulin (39).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This conclusion extends the evidence for the tubular excretion of creatinine as advanced by Shannon (21) and Shannon and Ranges (27), and confirms that reviewed elsewhere on the mechanism of excretion of inulin (39).…”
supporting
confidence: 91%
“…Shannon and Ranges (27) have, however, presented evidence to refute this view. They have shown that (a) the creatinine/inulin clearance ratio does not fall markedly with time if the plasma level is maintained by the continuous infusion of creatinine, (b) a second dose of creatinine elevates the clearance ratio, after this has been depressed by the lapse of time, towards the values observed shortly after a first dose, and (c) this elevation occurs only if the ratio has been depressed by virtue of the prolonged circulation of creatinine in the body.…”
mentioning
confidence: 98%
“…The PAH clearance, without an extraction correction factor, was used to measure changes in renal plasma flow. As facilities for inulin or mannitol clearances were not available, creatinine clearance was used as a reflection of glomerular filtration, although it is generally felt that inulin or mannitol better measure this in man (31,32). Creatinine/inulin ratios recently published (33,34) suggest, however, that creatinine clearance is a fairly good measure of glomerular filtration, especially when PAH or diodrast is administered concurrently.…”
Section: Methodsmentioning
confidence: 99%
“…Shannon and Smith [1935] claimed to establish the constancy of the renal clearance of inulin between plasma inulin levels of 50 and 400 mg./100 ml. Since extrapolation of the straight line which they constructed, relating the renal excretory rate of inulin and the corresponding plasma levels, passed through the point of origin, they concluded that the independence of inulin clearance and plasma levels still persisted at plasma levels below 50 mg./100 ml., and that the slope of the regression line represented the rate of glomerular filtration.…”
Section: Introductionmentioning
confidence: 99%